A Keyword Co-Occurrence Analysis of Research on Service Learning: Conceptual Foci and Emerging Research Trends - David Kongpiwatana Narong; Phillip Hallinger (MDPI AG, 2023)
Although a significant body of research has accumulated on service learning over the past seven decades, to date, no reviews have analyzed the entire multi-disciplinary literature. Thus, scholars lack systematic documentation of the scope of this literature, its thematic structure, and topical foci. This bibliometric review aimed to document these features of the service learning knowledge base. The review analyzed 5615 Scopus-indexed documents on service learning published between 1950 and 2022 through citation, co-citation, and keyword co-occurrence analyses. The analyses uncovered thematic and empirical foci associated with the theory, implementation, and effects of service learning. The review identified engineering education and problem-based learning as related topics of significant interest. In recent years, educators have increasingly experimented with the integration of other active teaching and learning methods into service learning programs. This review suggests that future research examine service learning from the perspectives of public policy, stakeholder engagement, and educating for sustainability. The field would also benefit from additional theorizing on the features that distinguish service learning from other active learning pedagogies.